2021
DOI: 10.3390/polym13183139
|View full text |Cite
|
Sign up to set email alerts
|

A Dyciandiamine-Based Methacrylate-Epoxy Dual-Cure Blend-System for Stereolithography

Abstract: In this research, an epoxy-based dual-cure system is developed and characterized for SLA additive manufacturing. Dual-cure systems consist of UV-curable acrylates and thermal active components. The second curing step offers an additional degree of freedom to design specific material properties. In this study, a blend of varying concentrations of an epoxy/curing agent mix, respectively, DGEBA, DICY and photocurable methacrylate, was used to create a material that is printable in the SLA process into a UV-cured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Comparing these results to those previously reported for blending acrylates and epoxides (Table S1, Supporting Information) indicates that in some cases, a higher Young's modulus and tensile strength can be achieved, [15,19,21,25] however, their Tg values are below 150 °C. Moreover, the flexural modulus evaluated by three-point bending measurements was 3.3 GPa which is in the same order of magnitude as other reported materials (Figure S11, Supporting Information).…”
Section: Alkylated Melamine As a Hardener For Baemasupporting
confidence: 77%
See 1 more Smart Citation
“…Comparing these results to those previously reported for blending acrylates and epoxides (Table S1, Supporting Information) indicates that in some cases, a higher Young's modulus and tensile strength can be achieved, [15,19,21,25] however, their Tg values are below 150 °C. Moreover, the flexural modulus evaluated by three-point bending measurements was 3.3 GPa which is in the same order of magnitude as other reported materials (Figure S11, Supporting Information).…”
Section: Alkylated Melamine As a Hardener For Baemasupporting
confidence: 77%
“…[13] Epoxy-acrylate hybrid systems have been previously molded, [14,15] and printed by Digital Light Processing (DLP). [16][17][18][19][20][21][22][23][24][25] In both methods, the resulting hybrid polymers usually have inferior mechanical properties compared to the epoxy resin without the acrylate component. The reported Young's modulus of the hybrid polymers is 0.036-2.59 GPa, with a maximum Tg of only 150 °C (Table S1, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Kuang et al used anhydride chemistry to cure the epoxides thermally after 3D printing of a (meth)­acrylate resin . Furthermore, Drummer et al proposed a dicyandiamine-based methacrylate epoxy blend system for SLA …”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of photopolymerizable IPNs contain diglycidyl ether of bisphenol A (BADGE od DGEBA) as an epoxy monomer or the (meth)­acrylate modification (bis-GMA), as they impart good thermal resistance and (thermo)­mechanical properties to the photopolymer networks. , But, bisphenol A is known to act as a reprotoxic R2 substance and was originally used as an artificial estrogen. Hence, this endocrine disruptor may lead to alterations in both the immune and reproductive systems .…”
Section: Introductionmentioning
confidence: 99%
“…While a mixed system approach offers more flexibility in controlling viscosity, cross-linking density, and backbone properties, miscibility is a concern both prior to printing and during polymerization, which can impact the morphology and final properties, and is strongly dependent on the polymerization kinetics and thermodynamic miscibility of the polymer blend . Both curing kinetics and miscibility are dependent on factors such as curing and postcuring times, cure temperatures, and cure sequence. Previous studies of dual-cure resins have investigated the effects of different UV postcure times, postcure temperatures, curing sequences, postcure processes, and resin formulations , on thermo-mechanical properties. For example, Obst et al investigated the influence of UV exposure time on a dual-curing system and found that longer exposure time reduced the effect of the second-stage thermal curing, while Kuang et al , photocured and thermally cured epoxy/acrylate mixtures at 100 °C for 2 h followed by 160 °C for 1 h and observed a single T g and concluded that they had formed an interpenetrating polymer network (IPN) with no macroscale phase separation.…”
Section: Introductionmentioning
confidence: 99%